2020
DOI: 10.1177/1745499920958855
|View full text |Cite
|
Sign up to set email alerts
|

Examining the linkage between class attendance at university and academic performance in an International Branch Campus setting

Abstract: The relationship between class attendance and academic performance has been an important area of research, with a positive association being posited between the two. The setting for our study is an International Branch Campus (IBC) of a British university that needs to demonstrate the quality of its service delivery both to the parent institution and to the fee-paying students. We employ a dataset of over 900 students in an undergraduate degree programme and subject it to statistical techniques, namely quantil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Poor attendance is concerning as class attendance is often predictive of grades in higher education and is strongly predictive of failure rates ( 37 – 39 ). For example, 1 study of nearly 1,000 undergraduates reported that course failure rates dropped by 80% for students who attended at least 75% of class sessions for a course ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor attendance is concerning as class attendance is often predictive of grades in higher education and is strongly predictive of failure rates ( 37 – 39 ). For example, 1 study of nearly 1,000 undergraduates reported that course failure rates dropped by 80% for students who attended at least 75% of class sessions for a course ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mandatory attendance is one method to increase class attendance ( 37 ). However, students often report that mandatory attendance policies would not improve their educational planning and, therefore, class attendance ( 41 , 42 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodologies used in the literature to analyse the relationship between class attendance and students' academic performance can be classified into three groups (Karnik et al, 2020). The first group includes studies that use correlations to examine the linear relationship between these two variables (Credé et al, 2010;Gough et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students' attendance and absenteeism have long been a contention for educational institutions (Ezeofor & Georgewill, 2020;Kovelan et al, 2019). In several studies, class attendance has been linked with students' academic performance and has affected learner graduation (Chenneville & Jordan, 2008;Karnik et al, 2020;Nordmann et al, 2019).…”
Section: Figure 4 Smart Classroommentioning
confidence: 99%